In-situ aircraft measurements of wind farm wake effects during the AWAKEN campaign in Oklahoma (September 2023), flight AWAKEN_20230929_1222 - Konrad Bärfuss; Jonas Spoor; Ulf Bestmann; Matthias Cremer; Thomas Feuerle; Maik Angermann; Mark Bitter; Astrid Lampert (PANGAEA, 2025)
The AWAKEN (American WAKE ExperimeNt) aircraft measurement campaign was conducted in September 2023 to investigate the interactions between wind farms and the atmospheric boundary layer (ABL) in the Southern Great Plains of Oklahoma, USA. The campaign involved 20 research flights conducted close to hub height using the research aircraft Cessna F406 with call sign D-ILAB of TU Braunschweig. Parts of the flight patterns were aligned perpendicular to the prevailing wind direction downwind of the wind farms King Plains and Armadillo Flats. These flights were designed to capture the effects of stable atmospheric conditions on wind speed and turbulence during early morning hours. In addition to flight legs perpendicular to the wind direction, vertical profiles up to an altitude of 1 km were included regularly to investigate atmospheric stability and wind profiles, in particular the phenomenon of low level jets. The resulting data include wind speed, turbulence intensities, and temperature distributions at different altitudes and distances from the wind farms. These measurements complement stationary data and provide valuable insights into the spatial and temporal variability of the wind field and vertical atmospheric stratification downwind of onshore wind farms. The dataset aims to improve wake models and optimize energy production from wind farms. This dataset is part of a broader effort to enhance power output prediction and ensure network stability with increasing reliance on variable renewable energy sources. The participation of the research aircraft of TU Braunschweig in the AWAKEN experiment was funded by the Klaus Tschira Stiftung GmbH (Germany) under Contract No. 03.006.2023.
In: Bärfuss, K et al. (2025): In-situ aircraft measurements of wind farm wake effects during the AWAKEN campaign in Oklahoma (September 2023) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.984783